Teoría en investigaciones de posgrado de la Escuela de Salud Pública de la Universidad del Valle, Colombia, 1990-2004 (2009)
ABSTRACT: To provide evidence about the utilization of theories and theoretical models in the postgraduate research carried out by the School of Public Health, University of Valle, in Cali, Colombia. Methodology: in March 2005, the total amount of 540 reports and theses submitted between 1965 and 2004 to get master’s degree in the School were analyzed. Based on a set of established criteria and using a questionnaire previously designed and applied, a trained reviewer recorded the variables defined for this study. Results: 405 reports and theses submitted between 1990 and 2004 (75% of the universe) were included in this study; most of them were focused on public health (33%) and health management (31%), followed by those devoted to occupational health (20%) and epidemiology (16%). The major amount based on a quantitative focus were present in the last two types of studies. In reports, 52% included a theoretical framework, 27% a conceptual framework and 14% a referential framework. A total of 33 (8%) out of 405 reports included a theory or a theoretical model, but only 3 (0.7%) developed them in-depth. Conclusions: the use of theories and theoretical models in public health for purposes of thematic, methodological and analytical orientation in the analyzed studies is low; and a very low rigor is also noticeable when using this theoretical basis.